Mucins and gastrointestinal malignancy. A new approach to the interpretation of biopsies. - Filipe, M. I. (Acta Médica Portuguesa, 1979)
Mucous secretion in the gastrointestinal tract shows regional variations: neutral mucins predominate in the gastric mucosa, sialic acid-rich compounds in the small intestine and sulphated mucins in the large intestine; glycoprotein synthesis also varies with cell maturation from crypt to surface epithelium. Changes in these normal mucous patterns have been observed in carcinoma and particularly in the non-neoplastic adjacent mucosa: A) In the stomach extensive and severe intestinal metaplasia with increased sulphomucin secretion is often associated with carcinoma; B) In the small intestine alteration in the proportion of various sialic acids and the presence of sulphated material are found in areas adjacent to carcinoma; C) In the large intestine harbouring carcinoma sialomucins become predominant with decrease or absence of sulphated radicals. Alterations in glycoprotein synthesis have been implicated in malignancy and we believe that the changes described above may represent a feature of malignant transformation and thus be of value in the interpretation and possibly detection of early cancer.